2018
DOI: 10.15406/mojap.2018.05.00211
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation effects of prenatal stress by early postnatal stimulation in different research models

Abstract: Prenatal stress alters the pattern of corticoid secretion and affects transplacentally the fetus hypothalamic-pituitary-adrenal axis (HPA) in different animal models. Early postnatal stimulation or handling results in an increase in maternal care to the offspring what reverts the effects of prenatal stress on the alterations produced in the HPA axis. In this revision article we describe and discuss the underlying mechanism present and discuss the mechanisms leading to causing imbalance produced by prenatal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that increased levels of Rab GDIα expression in the HC, when mice are injected with MK 801. Mineralocorticoid receptor and glucocorticoid receptor mRNA levels are downregulated in PRS mice [ 56 ].…”
Section: Animal Models Of Schizophreniamentioning
confidence: 99%
“…Studies have shown that increased levels of Rab GDIα expression in the HC, when mice are injected with MK 801. Mineralocorticoid receptor and glucocorticoid receptor mRNA levels are downregulated in PRS mice [ 56 ].…”
Section: Animal Models Of Schizophreniamentioning
confidence: 99%